Immunotherapy of colorectal cancer - Jäger, Dirk; Halama, Niels; Zörnig, Inka; Klug, Paula; Krauß, Jürgen; Haag, Georg Martin (Oncology research and treatment, 2016)
It is known that the immune response, reflected by high T cell infiltrates in primary tumors and metastases, influences the clinical course of colorectal cancer (CRC). Therefore, immunotherapy concepts have been adapted from other tumor entities, which typically rely on the activation of T cells in the tumor microenvironment (e.g. blockade of the immune checkpoint molecules PD-1 and CTLA-4). However, most of the strategies using the approved checkpoint inhibitors and/or combination strategies have more or less failed to produce impressive results in early phase trials in CRC. Therefore, a number of novel targets for checkpoint inhibition are currently in early phase clinical testing (TIM-3, Lag-3, OX40, GITR, 4-1BB, CD40, CD70). A simple activation of infiltrating T cells will not, however, lead to a meaningful anti-tumor response without modulating the environmental factors in CRC. Thus, it is absolutely necessary to improve our understanding of the complex regulation of the tumor microenvironment in CRC to design individual combination treatments leading to effective immune control.
Gesehen am 16.08.2019